MORAL DIMENSION OF HUMAN ESSENCE FROM THE PERSPECTIVE OF THE PRIEST (Pedagogy of Higher and Secondary Education, 2008)
In this article orthodox priest A. Harmash’s point of view on the problem of moral establishment of modern man and the influence of system of education is analysed.